- #1

- 24

- 0

Imagine we have a box suspended to the ceiling by a rope of negligible mass, the net force looks like:

∑F=T-Fg=0

T=Fg

where T and Fg are equal in magnitude but opposite in direction.

If we cut the rope, the box is in free fall and ∑F=Fg, and this equation is similar to T=Fg

but Fg and ∑F have the same direction and T and Fg have opposite directions.

I am really confused about this, and it must come from the sign convention while using vector notation and when you drop the vector notation,

Thanks for the attention :)

∑F=T-Fg=0

T=Fg

where T and Fg are equal in magnitude but opposite in direction.

If we cut the rope, the box is in free fall and ∑F=Fg, and this equation is similar to T=Fg

but Fg and ∑F have the same direction and T and Fg have opposite directions.

I am really confused about this, and it must come from the sign convention while using vector notation and when you drop the vector notation,

Thanks for the attention :)

Last edited: